2018
DOI: 10.1055/s-0038-1676192
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-free life in India: Application of survival function analysis

Abstract: Background:India being a diverse country has an assortment of various socio-economic and demographic structures. These socio-economic and demographic factors often intervene with the diabetes-free survival in any geographical region. The present study explores diabetes-free survival patterns of adult respondents with respect to various socio-economic and demographic factors in eighteen states of India with better demographic indicators. Material and Methods:The study utilizes data from the fourth rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…India is a large and diverse country ( 3 ); which when combined with the rigid social stratification, it acts as the root cause for the social and economic inequalities, which in turn, reciprocates in the form of disparities in opportunities and political and economic decision-making ( 2 ). The Aboriginal population, which comprises around 750 tribes, and account for 8.6 percent of the Indian population, is considered the most vulnerable sub-group in the country ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…India is a large and diverse country ( 3 ); which when combined with the rigid social stratification, it acts as the root cause for the social and economic inequalities, which in turn, reciprocates in the form of disparities in opportunities and political and economic decision-making ( 2 ). The Aboriginal population, which comprises around 750 tribes, and account for 8.6 percent of the Indian population, is considered the most vulnerable sub-group in the country ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…7,10,11 This predisposition of the Indian population could be linked to the genetic makeup of the population. 12 Evidence generated from existing literature, suggests that, men have higher rates of mortality, while, women report higher prevalence of morbidity as compared to that of men. 4,13 This situation can be explained by utilizing two broad theories, namely, the biological and the psychosocial.…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted in India, employing the life table methodology, revealed that the likelihood of maintaining a diabetes-free life diminishes with age. Specifically, only 30% of the overall participants remained free of diabetes beyond the age of 77 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, several previous studies have also noted an elevated diabetes risk among males [ 10 18 ]. An Indian study specifically highlighted that the likelihood of remaining diabetes-free is notably lower for men compared to women, particularly for urban residents and those belonging to higher socioeconomic classes [ 23 ]. This investigation utilized data from the India Human Development Survey (IHDS) and discovered that only 26% of urban males and 33% of urban females remained diabetes-free until the age of 73 in India [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation